Effects of organic additives on film characteristics of flexible PEDOT:PSS/latex - da Silva, Rafael Aparecido [UNESP]; Boratto, Miguel Henrique [UNESP]; Aguiar, Roberto Ramos [UNESP]; Lima, João Victor Morais [UNESP]; Martins, Lucas Michelão [UNESP]; Nozella, Natan Luis [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Springer Nature, 2023)
In this work, organic additives were incorporated into a flexible conductive film based on natural rubber latex (NRL) and PEDOT:PSS to improve both its electrical and mechanical properties. The additives, which included carbon black (CB), reduced graphene oxide (rGO), and polypyrrole (PPy), were dispersed in the PEDOT:PSS with NRL film. The resulting films exhibited enhanced electrical and mechanical stability, as well as improved responsiveness to compressive stimuli. The CB acted as a crosslinker of isoprene chains and enhanced charge percolation, providing higher electrical and mechanical stability. The rGO contributed to increased mechanical strength and slower relaxation time, while the PPy contributed to percolation and a higher number of conductive polymer chains in the blend. The best electromechanical performance was achieved with a blend containing 3.5 CB, 10.0 rGO, and 5.0 PPy, with initial resistivities of 2.3 ± 0.2 Ω cm, 3.4 ± 0.2 Ω cm, and 1.8 ± 0.2 Ω cm, and moduli of elasticity of 90.4 KPa, 85.7 KPa, and 134.6 KPa, respectively. These improvements suggest that the new compositions may be useful for a range of applications, including bioelectronics and piezoresistive devices.